Mechanisms of alloimmunization in sickle cell disease. Issue 6 (November 2019) - Hudson, Krystalyn E.; Fasano, Ross M.; Karafin, Matthew S.; Hendrickson, Jeanne E.; Francis, Richard O.
Abstract : Purpose of review: Red blood cell (RBC) transfusion is an important treatment for some complications of sickle cell disease (SCD). On the contrary, transfusion may lead to alloimmunization to RBC antigens, with such alloantibodies putting patients at risk for acute or delayed hemolysis, and increasing the difficulty of finding compatible RBCs. Patients with SCD are more susceptible to developing RBC alloantibodies than other multiply transfused patient populations, for reasons that are not completely understood. In this review, we summarize the available data about risk factors and underlying mechanisms associated with RBC alloimmunization in SCD. Recent findings: Although RBC antigen matching between blood donors and transfusion recipients can decrease alloimmunization, complete matching at all loci is not feasible. Patients with SCD show evidence of increased inflammation at baseline and in times of illness. Resultant changes to the innate and adaptive immune systems presumably influence the development of RBC alloantibodies as well as RBC autoantibodies. Summary: The inflammation and immune dysregulation associated with SCD may be therapeutic targets for preventing the formation of antibodies and/or for mitigating the dangers of existing RBC alloantibodies. As long as RBC transfusion therapy remains an important treatment for SCD, the quest to improve its safety profile will continue.